2008
DOI: 10.1143/jjap.47.6181
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Scale Manipulation and Ultrasonic Cutting Using an Atomic Force Microscope Controlled by a Haptic Device as a Human Interface

Abstract: We describe a nanometer-scale manipulation and cutting method using ultrasonic oscillation scratching. The system is based on a modified atomic force microscope (AFM) coupled with a haptic device as a human interface. By handling the haptic device, the operator can directly move the AFM probe to manipulate nanometer scale objects and cut a surface while feeling the reaction from the surface in his or her fingers. As for manipulation using the system, nanometer-scale spheres were controllably moved by feeling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Our results showed that the vibration cutting with probe oscillation is very useful for the dissection of biological samples prepared and dried for SEM observation. We previously used the vibration cutting method for dissecting different samples including the soft polymers and dried collagen fibrils (Iwata et al, 1999(Iwata et al, , 2008. These previous studies also revealed the usefulness of vibration cutting for dissecting both hard samples and elastic soft samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the vibration cutting with probe oscillation is very useful for the dissection of biological samples prepared and dried for SEM observation. We previously used the vibration cutting method for dissecting different samples including the soft polymers and dried collagen fibrils (Iwata et al, 1999(Iwata et al, , 2008. These previous studies also revealed the usefulness of vibration cutting for dissecting both hard samples and elastic soft samples.…”
Section: Discussionmentioning
confidence: 99%
“…This emerging technology has been widely used in various fields such as games, computer-aided design, medical simulations, and remote control robotics. Recently, haptic technologies have been also introduced in nanometerscale manipulations of materials using the atomic force microscope (AFM) (Guangyong et al, 2005;Iwata et al, 2008). These studies showed that an operator can directly move an AFM probe on the sample surface and feel the response from its surface during AFM manipulation by using the haptic device.…”
Section: Compact Afm Manipulatormentioning
confidence: 99%
“…A homemade system consisting of the AFM, controller, and software was modified to connect the haptic device for the manipulation [38]. With respect to lateral movements in the x and y directions, a signal from the haptic device is sent to the personal computer, and then the signal is sent to the piezo drive circuit passing through a digital-to-analog converter.…”
Section: Bmentioning
confidence: 99%
“…Sitti et al 6 used a one degree-of-freedom haptic device, where the Z probe position is controlled using a proportional-integral (PI) controller that tracks the haptic position, and the force-feedback felt in the haptic device is converted from the AFM-probe measured force using a proportional-differential (PD) controller, and adjusted to the applied user force. Teleoperation of an AFM has also been utilised by Iwata et al 7 to perform manipulation and ultrasonic cutting, where the force-feedback applied in the haptic device is adjusted to follow the probe position. During manipulation the force applied by the user is converted to a new setpoint for the atomic force probe.…”
Section: Reviewmentioning
confidence: 99%